(untitled) (Heritage, 2023)
The spread of digital technologies and their power to connect billions of people around the world, has enabled modern society to communicate more efficiently, access information, do business, but also have fun. However, there are many examples in which this possibility is abused for cyber-criminal activities, among which is certainly cyber terrorism. Through the activities of traditional terrorism, terrorists try to provoke anxiety in the population, choosing targets randomly or selectively, against which violence is committed, with the intention of serving as an example to other members of society. Such incitement to fear is precisely the means of terrorist individuals and groups, who want to put pressure on the government and the general public to meet their demands. Recently, there are more and more examples in which such activities are moving (with more or less success) to the digital environment. Cyber ​​terrorism is a means of spreading radical ideology, propaganda, recruiting like-minded people, but also organizing cyber terrorist attacks. The advantage that a terrorist activist sees in using such methods is certainly the possibility to remain anonymous and easily hide in the cyber world. Cybercriminals easily adapt and find new methods of committing cyberbullying, which must be a call to governments to regulate legislation in a synchronized effort, but also to form expert teams that will identify, prevent and adequately sanction such criminal activities and protect their population and critical infrastructure. This paper seeks to bring closer and present information to the academic community, but also to experts in the field of cyber terrorism that can help them improve strategies for recognizing and defending against such cyber activities. The main goal of this paper is to analyze the collected information from the available scientific literature and to offer new guidelines in order to reduce such activities to a minimum in the near future.